Pengaruh Jenis Cabai dan Metode Processing terhadap Mutu Benih Cabai - Chotimatul Azmi; Astiti Rahayu; Arsiliya Putri; Siswi Wahyu Astuti; Ira Anggraini (UIN Sunan Gunung Djati Bandung, 2023)
In addition to plant treatment in the field, the processing method also effects to the quality of chili seeds. Information on this matter is still limited. This research was conducted to determine the effects of chili type and processing method on chili seed quality. The treatments of three types of chillies (big, curly and cayenne) with two processing methods (manual wet and by machine) was carried out at the Vegetables Crops Research Institute from February to May 2018. Seed quality observations were carried out using the ISTA method for parameters of seed moisture content and germination. The result showed that the seed water content was affected by the type of chili and the processing method. Manual processing of chili seeds produces seeds with lower seed moisture content (7.86%) compared to machine processing (8.44%). Seed moisture content from the lowest to the highest was successively produced by curly chili, big chili and cayenne chili at 7.39%, 8.01%, and 9.05%. The germination of seeds from manual processing was significantly higher than that from machine processing (39.83%). The germination of curly chili seeds (53.13%) was not significantly different from that of big chili (49.63%) but significantly different from that of cayenne pepper (33.00%).